Financial Stress Relationship with Work Life and Financial Well-Being - Suna Ozyuksel (European Scientific Journal, ESJ, 2022)
In the survey, which examines employees’ status with respect to and the sources of stress as well as its effects on the workforce, a version of the “Financial Well-Being Scale” validated to Turkish has been used and stress levels, generalized anxiety, work performance and psychological resilience levels were measured. We have seen that as the age and education levels of the participants increase, their financial well-being levels improve and their financial stress levels decrease. It is understood that when the financial wellbeing improves/financial stress decreases, this leads to decrease in anxiety level, increase in psychological resilience and im-provement in job performance. We also found that even though participants had high income levels, sav-ings/investments, and no debt; they felt high / the highest levels of financial stress mainly due to high inflation, macroeconomic instability, not knowing how to make the right investments to protect their savings against macroeconomic instability and high level of expenses. We have concluded that financial stress causes them to be depressed at work, unable to concentrate on their work and decreases their perfor-mance.